"It is me who endures but my family that suffers": social isolation as a consequence of the household cost burden of Buruli ulcer free of charge hospital treatment. - Koen Peeters Grietens; Alphonse Um Boock; Hans Peeters; Susanna Hausmann-Muela; Elizabeth Toomer; Joan Muela Ribera (PLoS Neglected Tropical Diseases, 2008)
Despite free of charge biomedical treatment, the cost burden of Buruli ulcer disease (Bu) hospitalisation in Central Cameroon accounts for 25% of households' yearly earnings, surpassing the threshold of 10%, which is generally considered catastrophic for the household economy, and calling into question the sustainability of current Bu programmes. The high non-medical costs and productivity loss for Bu patients and their households make household involvement in the healing process unsustainable. 63% of households cease providing social and financial support for patients as a coping strategy, resulting in the patient's isolation at the hospital. Social isolation itself was cited by in-patients as the principal cause for abandonment of biomedical treatment. These findings demonstrate that further research and investment in Bu are urgently needed to evaluate new intervention strategies that are socially acceptable and appropriate in the local context.